2017
DOI: 10.1111/jorc.12189
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with nurse‐led chronic kidney disease clinics: A multicentre evaluation

Abstract: SUMMARY Background There is growing international evidence that nurse‐led chronic kidney disease (CKD) clinics provide a comprehensive approach to achieving clinical targets effective in slowing the progression of CKD. Across Queensland, Australia, these clinics have been established in many renal outpatient departments although patient satisfaction with these clinics is unknown. Objectives To measure patient satisfaction levels with CKD nurse‐led clinics. Method This was a cross‐sectional study undertaken at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…Similar results have been reported with other nurse‐led clinics (i.e. clinics being led by Registered Nurses, specialist nurses and/or nurse practitioners, with varying degrees of autonomy and responsibility) in areas such as orthopaedics (Flynn, 2005), kidney disease (Coleman et al., 2017), community medicine (Kant et al., 2018) and arthritis care (Garner et al., 2017). This review highlights the need for research with thorough methodologies, focused on outcomes, to inform evidence‐based decisions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results have been reported with other nurse‐led clinics (i.e. clinics being led by Registered Nurses, specialist nurses and/or nurse practitioners, with varying degrees of autonomy and responsibility) in areas such as orthopaedics (Flynn, 2005), kidney disease (Coleman et al., 2017), community medicine (Kant et al., 2018) and arthritis care (Garner et al., 2017). This review highlights the need for research with thorough methodologies, focused on outcomes, to inform evidence‐based decisions.…”
Section: Discussionsupporting
confidence: 77%
“…The level of evidence and lack of experimental trials in other types of nurse practitioner-led clinics have been identified in various systematic reviews whereby firm conclusions could not be drawn and more research was warranted (Leonard, 2006;Shah & Deswal, 2016;Whiteford et al, 2016). Mullins et al (2016) (Flynn, 2005), kidney disease (Coleman et al, 2017), community medicine (Kant et al, 2018) and arthritis care (Garner et al, 2017). This review highlights the need for research with thorough methodologies, focused on outcomes, to inform evidence-based decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet we acknowledge the systems barriers to change that reduce uptake of person-centred innovation in healthcare [ 66 ]. There are opportunities for this intervention to be delivered at existing nurse-led CKD clinics (e.g., [ 67 ]), or by nurses alongside routine clinical appointments at outpatient clinics. There is also potential for practices such as this to attract additional funding, with the current international focus on PCC in healthcare practice [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing burden of chronic disease, across Australia there are an increasing number of nurse practitioner-led clinics conducted in public hospital outpatient departments or community healthcare centres although these clinics tend to align with the medical specialty model of service delivery. Nevertheless, nurse practitioner-led services are delivering on the triple aim of healthcare transformationenhancing patient experience, improving population health and reducing costs-while building future workforce capacity for integrated care (Coleman et al, 2017;Craswell et al, 2018;Douglas et al, 2018). This paper describes a novel, community-based Integrated Chronic Disease Nurse Practitioner (ICDNP) clinic and profiles the patient characteristics and clinical targets at entry to the clinic.…”
Section: Nurse Practitioner-led Servicesmentioning
confidence: 99%